Pedagogical potential of the course «Sports wrestling with teaching methods» in the training of future physical education teachers - Abdullaev, Altai; Абдуллаєв, Алтай Карам-Огли; Абдуллаев, Алтай Карам-Оглы; Rebar, I. (My University, 2021)
The purpose of teaching the course is to acquire skills and abilities of teaching wrestling in educational institutions and the formation of physical culture of the future teacher.
Keywords: physical culture; sports wrestling; wrestling workshop